Lithium ion battery diaphragm, preparation method thereof and lithium ion battery

By dispersing different melting points or softening points in lithium -ion battery septum, it solves the problem that the diaphragm is difficult to take into account the problem of high adhesion, heat resistance and pore permeability, and realize the improvement of higher performance septum and battery performance. Essence

CN119361970AInactive Publication Date: 2025-01-24JIANGSU ADVANCED MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411931757.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult for existing lithium-ion battery separators to take into account high adhesion, heat resistance and channel permeability at the same time, resulting in limited battery performance.

Method used

By dispersing the first polymer and second polymers with different melting points or softening points, they are dispersed and dispersed in the coating of the diaphragm, optimizing the adhesive and thermal coating between the diaphragm and the thermal coating.

Benefits of technology

While improving the adhesive between the diaphragm and the polar tape, the problem of optimizing the obstacles of the diaphragm and thermal coating tunnel has obtained a higher -performance diaphragm, which improves the battery multiplier and electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361970A_ABST
    Figure CN119361970A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery diaphragms, in particular to a lithium ion battery diaphragm, a preparation method thereof and a lithium ion battery. The lithium ion battery diaphragm comprises a base material and a polymer coating arranged on at least one surface of the base material, the polymer coating comprises a plurality of dispersedly arranged dotted structures, and the dotted structures are annular and / or island-shaped; the diameter of a circumcircle of the dotted structure is Z, and the polymer coating contains a first polymer and a second polymer in a range with the center point of the circumcircle as the circle center and the radius of 8Z; the melting point or softening point of the first polymer is not more than 90 DEG C; the melting point or softening point gt of the second polymer; 90 DEG C; according to the invention, the first polymer and the second polymer with different melting points or softening points are dispersed and arranged at the same time, so that the advantages of different polymer materials can be played, and the problem of pore channel blockage of the diaphragm and the heat-resistant coating can be solved while the adhesion between the diaphragm and a pole piece is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery separators, and in particular to a lithium ion battery separator and a preparation method thereof, and a lithium ion battery. Background Art

[0002] In order to improve the performance of lithium-ion battery separators, researchers have developed coating materials represented by metal oxides to improve the heat resistance of separators, and polymer coatings with adhesive polymers as the main material to improve the adhesion between separators or heat-resistant coatings and positive and negative electrodes. Among them, adhesive coatings are mostly achieved by spraying.

[0003] In order to improve the charge and discharge rate of lithium ions in the battery, the polymer coating is arranged in a dispersed manner, which is different from the full coverage coating method of the heat-resistant coating. While playing its bonding role, the dispersed polymer points are formed by the accumulation of polymer particles. They have a certain height and play a supporting role to facilitate the penetration of the electrolyte between the diaphragm or heat-resistant coating and the electrode.

[0004] However, the use of a single polymer material for the separator often cannot take into account multiple advantages at the same time. For example, some polymer materials have excellent adhesion, but their melting point / softening point is low. Under hot pressing conditions, these polymer materials are easy to flow, causing blockage of the pore structure of the separator and heat-resistant coating. Some polymer materials are not easy to penetrate into the porous structure of the separator and heat-resistant coating, resulting in obstruction of the lithium ion transmission channel. They are excellent separator materials, but have poor adhesion performance.

[0005] Therefore, it is of great significance to provide a diaphragm that can take into account multiple advantages at the same time and has higher performance.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The first purpose of the present invention is to provide a lithium-ion battery separator. By simultaneously dispersing and arranging a first polymer and a second polymer having different melting points or softening points, the advantages of different polymer materials can be brought into play. While improving the adhesion between the separator and the electrode, the pore blockage problem of the separator and the heat-resistant coating can be optimized, thereby obtaining a separator with multiple advantages and higher performance.

[0008] The second object of the present invention is to provide a method for preparing a lithium-ion battery separator, which has the advantages of simple operation, short process and suitability for mass production.

[0009] A third object of the present invention is to provide a lithium ion battery having excellent electrochemical performance.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: The present invention first provides a lithium-ion battery separator, comprising a substrate and a polymer coating arranged on at least one surface of the substrate, wherein the polymer coating comprises a plurality of dispersed point structures, wherein the shape of the point structures comprises a ring shape and / or an island shape; the diameter of the circumscribed circle of the point structures is Z, and within a range with the center point of the circumscribed circle as the center and 8Z as the radius, the polymer coating contains a first polymer and a second polymer; the melting point or softening point of the first polymer is ≤90°C; the melting point or softening point of the second polymer is >90°C.

[0011] Furthermore, the diameter of the circumscribed circle of the dot-like structure is 100 μm to 1000 μm.

[0012] Furthermore, the diameters of the circumscribed circles of two adjacent dot-like structures are X and Y respectively, and the distance between the centers of the two circumscribed circles is D, and D is greater than the maximum value of X and Y, and D is less than 5 times the maximum value of X and Y.

[0013] Furthermore, the D is greater than 1.25 times the maximum value of the X and the Y.

[0014] Furthermore, the distance between the centers of the circumscribed circles of two adjacent dot-shaped structures is 100 μm to 1500 μm.

[0015] Furthermore, the shape of the outer contour of the orthographic projection of the dot-shaped structure on the substrate includes at least one of a circle, an ellipse and a quasi-circle.

[0016] Furthermore, the dot structures are arranged in a dot matrix.

[0017] Furthermore, the height of the dot-like structure is 1 μm to 20 μm.

[0018] Further, the first polymer includes at least one of polyvinylidene chloride, polyacrylate, polyvinyl acetate, polyethylene oxide, polyvinylidene fluoride, polypropylene oxide, styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, acryl rubber, butyl rubber, fluororubber, polyepichlorohydrin, polyphosphazene, polyvinylpyridine and styrene-butadiene rubber.

[0019] Furthermore, the melting point or softening point of the first polymer is 30°C to 90°C.

[0020] Furthermore, the median particle size of the first polymer is 0.1 μm to 20 μm.

[0021] Further, the second polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene polymer, polyacrylate, polystyrene, polyacrylonitrile, polytetrafluoroethylene, polymethacrylate, ethylene-vinyl acetate copolymer, polyester, polyamide, polyurethane, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene-acrylate copolymer, acrylated styrene-butadiene copolymer, phenolic resin, epoxy resin, polyvinyl pyrrolidone and polysulfone.

[0022] Furthermore, the median particle size of the second polymer is 0.1 μm to 20 μm.

[0023] Furthermore, the mass ratio of the first polymer to the second polymer in the polymer coating is 0.001-99.999:0.001-99.999.

[0024] Furthermore, the area coverage of the polymer coating on the substrate is 5% to 40%.

[0025] Furthermore, the single-sided loading of the polymer coating is 0.2 g / m 2 ~1.5g / m 2 , preferably 0.4g / m 2 ~1g / m 2 .

[0026] Furthermore, the substrate includes at least one of PE, PP, non-woven fabric, PET, PVDF, PU, ​​PA, PI, organic-inorganic blended film and PP / PE / PP composite film.

[0027] Furthermore, the polymer coating also includes at least one of a binder, a dispersant and a thickener.

[0028] Furthermore, a heat-resistant coating is included between the substrate and the polymer coating, and the heat-resistant coating contains inorganic materials, and the inorganic materials include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

[0029] The present invention further provides a method for preparing the lithium ion battery separator, comprising the following steps: coating a first slurry containing a first polymer and a second slurry containing a second polymer on at least one surface of a substrate respectively, and then drying.

[0030] The present invention also provides a lithium ion battery, comprising the lithium ion battery separator.

[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) The lithium-ion battery separator provided by the present invention can give full play to the advantages of different polymer materials by simultaneously dispersing and arranging the first polymer and the second polymer with different melting points or softening points. It can improve the adhesion between the separator and the electrode while optimizing the problem of pore blockage of the separator and the heat-resistant coating, thereby obtaining a separator with multiple advantages and higher performance, thereby improving the battery rate.

[0032] (2) In the lithium-ion battery separator provided by the present invention, the first polymer and the second polymer are evenly distributed, which improves the consistency of the separator and enhances the battery quality.

[0033] (3) The lithium-ion battery separator provided by the present invention has good consistency in separator thickness and consistency in the bonding force between the separator and the electrode after hot pressing, thereby improving the electrochemical performance of the separator and the battery made therefrom. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 A schematic diagram of the structure of the lithium-ion battery separator provided by the present invention; Figure 2 Another schematic diagram of the structure of the lithium-ion battery separator provided by the present invention; Figure 3 This is a diagram showing the arrangement of the dotted structures in the lithium-ion battery separator prepared in Example 1 provided by the present invention; Figure 4 This is a diagram showing the arrangement of the dotted structures in the lithium-ion battery separator prepared in Example 2 provided by the present invention; Figure 5 This is a diagram showing the arrangement of the dotted structures in the lithium-ion battery separator obtained in Example 3 of the present invention; Figure 6 This is a diagram showing the arrangement of the dotted structures in the lithium-ion battery separator prepared in Example 4 provided by the present invention; Figure 7 This is a diagram showing the arrangement of the dotted structures in the lithium-ion battery separator obtained in Example 5 provided by the present invention; Figure 8 This is a diagram showing the arrangement of the dotted structures in the lithium-ion battery separator obtained in Example 6 provided by the present invention. DETAILED DESCRIPTION

[0036] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0037] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0038] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0039] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0040] In a first aspect, the present invention provides a lithium ion battery separator, such as Figure 1 The structure schematic diagram of the lithium-ion battery separator provided by the present invention is shown, specifically a top view. The lithium-ion battery separator includes a substrate and a polymer coating disposed on at least one surface of the substrate, and the polymer coating includes a plurality of dispersed point structures. Among them, the number of the point structures is multiple, which can be two, three, five, eight, ten, twenty, thirty, fifty, seventy, one hundred or more. Among them, the substrate includes a porous substrate.

[0041] See also Figure 1 The shape of the dot-like structure includes ring-like and / or island-like. It can be understood that the dot-like structure is a protrusion with a certain height. Among them, the ring-like shape refers to a ring-like shape with a hollow center, and the island-like shape refers to a shape with a protrusion on the outside and the height of the protrusion is greater than the height at the center.

[0042] The diameter of the circumscribed circle of the dot-like structure is Z, and within the range of 8Z as the radius (preferably within the range of 5Z as the radius, and more preferably within the range of 3Z as the radius) with the center point of the circumscribed circle as the center, the polymer coating contains the first polymer and the second polymer. That is, both the first polymer and the second polymer should exist within a certain range, so that the advantages of the first polymer and the second polymer can be simultaneously exerted, thereby improving the comprehensive performance of the diaphragm. And in this way, the first polymer and the second polymer with specific different physical and chemical properties can be uniformly distributed.

[0043] It can be understood that the polymers in the ring-shaped dot-like structure and the island-shaped dot-like structure can be the same or different.

[0044] The melting point or softening point of the first polymer is ≤ 90° C., including but not limited to any one of 90° C., 80° C., 70° C., 60° C., 50° C., 40° C., and 30° C., or any range between two of them. The first polymer mainly plays a bonding role.

[0045] The melting point or softening point of the second polymer is greater than 90° C., including but not limited to any one of 95° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., 180° C., and 200° C., or any range between two of them. The second polymer mainly plays a supporting role.

[0046] It is understood that when the polymer is a crystalline polymer (such as PVDF, PVDF-HFP), the melting point of the first polymer is ≤90°C, and the melting point of the second polymer is >90°C. When the polymer is a non-crystalline polymer (such as polyacrylate), the softening point of the first polymer is ≤90°C, and the softening point of the second polymer is >90°C.

[0047] The lithium-ion battery separator provided by the present invention can give full play to the advantages of different polymer materials by simultaneously dispersing and arranging the first polymer and the second polymer with different melting points or softening points. It can improve the adhesion between the separator and the electrode while optimizing the problem of pore blockage of the separator and the heat-resistant coating, thereby obtaining a separator with higher performance that takes into account multiple advantages and improves the battery rate.

[0048] Furthermore, in the lithium-ion battery separator provided by the present invention, the first polymer and the second polymer are evenly distributed, thereby improving the consistency of the separator and enhancing the battery quality.

[0049] Specifically, the first polymer can provide high bonding strength between the diaphragm and the pole piece after hot pressing / cold pressing. The second polymer is not easy to flow and block holes after hot pressing / hot pressing, and its deformation after hot pressing / cold pressing will not be too large, which can prevent the first polymer from deforming too much and provide certain support. At the same time, the second polymer can also provide certain bonding strength.

[0050] In some specific embodiments, the diameter of the circumscribed circle of the dot-like structure is 100 μm to 1000 μm, including but not limited to any point value of 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm or a range value between any two of them.

[0051] In some specific embodiments, the diameters of the circumscribed circles of two adjacent dot-like structures are X and Y, respectively, and the distance between the centers of the two circumscribed circles is D, and D is greater than the maximum value of X and Y, and D is less than 5 times the maximum value of X and Y. In other words, the diameters of the circumscribed circles of two adjacent dot-like structures are X and Y, respectively, and the distance between the centers of the circumscribed circles of the two is D, the larger number of X and Y is MAX, and the smaller number of X and Y is MIN, then D>MAX, and D<5×MAX (i.e. 1 / 5<MAX / D). This can improve the consistency of the thickness of the diaphragm (make the thickness of the diaphragm uniform), as well as the consistency of the bonding force between the diaphragm and the pole piece after hot pressing, thereby improving the electrochemical performance of the diaphragm and the battery made therefrom, and improving the battery quality. Preferably, D is greater than 1.25 times the maximum value of X and Y, that is, D>1.25MAX and D<5MAX.

[0052] In some specific embodiments, the distance between the centers of the circumscribed circles of two adjacent dot-shaped structures is 100 μm to 1500 μm, including but not limited to any point value of 100 μm, 200 μm, 300 μm, 500 μm, 800 μm, 1000 μm, 1200 μm, 1500 μm or any range value between two of them. This is conducive to improving the adhesion between the diaphragm and the pole piece and reducing the clogging problem.

[0053] In some specific embodiments, the shape of the outer contour of the orthographic projection of the dot-shaped structure on the substrate includes at least one of a circle, an ellipse and a quasi-circle.

[0054] In some specific implementations, the dot structures are arranged in a dot matrix, which is beneficial to improving the consistency of the thickness of the diaphragm.

[0055] In some specific embodiments, the height of the dot-like structure is 1 μm to 20 μm, including but not limited to any point value of 1 μm, 2 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, and 20 μm, or a range of values ​​between any two of them. The dot-like structure having the above height range can play a supporting role to facilitate the penetration of the electrolyte between the diaphragm (or its heat-resistant coating) and the electrode.

[0056] In some specific embodiments, the first polymer includes at least one of polyvinylidene chloride, polyacrylate, polyvinyl acetate, polyoxyethylene, polyvinylidene fluoride, polyoxypropylene, styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, acryl rubber, butyl rubber, fluororubber, polyepichlorohydrin, polyphosphazene, polyvinylpyridine and styrene-butadiene rubber.

[0057] In some specific embodiments, the melting point or softening point of the first polymer is 30°C~90°C, including but not limited to any one of 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 78°C, 80°C, 85°C, 90°C or a range between any two of them.

[0058] In some specific embodiments, the median particle size of the first polymer is 0.1 μm to 20 μm, including but not limited to any point value of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.9 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 13 μm, 15 μm, 18 μm, 20 μm or any range value between two of them. The first polymer with such a particle size is conducive to its uniform dispersion.

[0059] In some specific embodiments, the second polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene polymer (i.e., vinylidene fluoride and hexafluoropropylene copolymer), polyacrylate, polystyrene, polyacrylonitrile, polytetrafluoroethylene, polymethacrylate, ethylene-vinyl acetate copolymer, polyester, polyamide, polyurethane, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene-acrylate copolymer, acrylated styrene-butadiene copolymer, phenolic resin, epoxy resin, polyvinyl pyrrolidone and polysulfone.

[0060] It is understandable that for the same polymer material, the melting point or softening point is different due to the difference in polymerization degree or relative molecular mass. Generally, the greater the relative molecular mass of the polymer, the higher its melting point or softening point. If it is the same type of polymer, its melting point or softening point can be controlled by copolymerizing different monomers.

[0061] In some specific embodiments, the median particle size of the second polymer is 0.1 μm to 20 μm, including but not limited to any point value of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.9 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 13 μm, 15 μm, 18 μm, 20 μm or any range value between two of them. The use of the second polymer with this particle size is conducive to its uniform dispersion.

[0062] In some specific embodiments, the mass ratio of the first polymer to the second polymer in the polymer coating is 0.001-99.999 (including but not limited to any one of 0.01, 0.05, 0.1, 0.5, 1, 3, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 95, 98, 99 or any range between two): 0.001-99.999 (including but not limited to any one of 0.01, 0.05, 0.1, 0.5, 1, 3, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 95, 98, 99 or any range between two). The mass ratio of the first polymer to the second polymer in the polymer coating is preferably 1-99: 1-99. The mass ratio of the first polymer to the second polymer in the polymer coating is more preferably 1-9: 1-9. This is beneficial to both improving the adhesion between the diaphragm and the pole piece and optimizing the pore blockage problem of the diaphragm and the heat-resistant coating.

[0063] In some specific embodiments, the polymer coating has an area coverage of 5% to 40% on the substrate, including but not limited to any point value of 5%, 8%, 10%, 12%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, or any range value between two of them. This is beneficial to improve the adhesion between the diaphragm and the pole piece and reduce the clogging problem.

[0064] In some specific embodiments, the single-sided loading of the polymer coating is 0.2 g / m 2 ~1.5g / m 2 ; Including but not limited to 0.2g / m 2 , 0.23g / m 2 , 0.25g / m 2 , 0.28g / m 2 , 0.3g / m 2 , 0.33g / m 2 , 0.35g / m2 , 0.37g / m 2 , 0.4g / m 2 , 0.5g / m 2 , 0.6g / m 2 , 0.8g / m 2 , 1g / m 2 , 1.2g / m 2 , 1.3g / m 2 , 1.5g / m 2 Any point value of or any range value between the two. This is beneficial to improve the bonding performance between the diaphragm and the pole piece.

[0065] In some specific embodiments, in order to further improve the bonding performance between the diaphragm and the electrode, the single-sided loading of the polymer coating is 0.4 g / m 2 ~1g / m 2 .

[0066] In some specific embodiments, the substrate includes at least one of PE, PP, non-woven fabric, PET, PVDF, PU, ​​PA, PI, organic-inorganic blended film and PP / PE / PP composite film.

[0067] In some specific embodiments, the polymer coating further comprises at least one of a binder, a dispersant and a thickener. The binder, the dispersant and the thickener may be any reagent commonly used in the art, and the present invention does not limit this. For example, sodium dodecyl sulfonate is used as a dispersant, and at least one of a copolymer of vinylidene fluoride and hexafluoropropylene, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polyhexafluoropropylene, etc. is used as a binder.

[0068] In some specific embodiments, a heat-resistant coating is further included between the substrate and the polymer coating, and the heat-resistant coating can improve the heat resistance of the diaphragm. The heat-resistant coating contains an inorganic material, and the inorganic material includes at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

[0069] In some specific implementations, the heat-resistant coating further includes a bonding material, wherein the bonding material may be any bonding agent commonly used in the art, and the present invention is not limited thereto.

[0070] In a second aspect, the present invention provides a method for preparing the lithium-ion battery separator, comprising the steps of coating a first slurry containing a first polymer and a second slurry containing a second polymer on at least one surface of a substrate, and then drying.

[0071] The method has the advantages of being simple, easy to operate, short process flow, low cost, and suitable for mass production.

[0072] In some specific embodiments, the coating method includes any coating method commonly used in the art, such as at least one of woodblock printing, screen printing, contact dotting technology, non-contact coating, and the like.

[0073] Among them, the coating method of woodblock printing includes: engraving a printing plate that can carry micro-droplets, transferring the coating slurry directly to the printing plate through a material box, or transferring it from the material box to the printing plate through an intermediate medium, and then transferring the micro-droplets carried by the printing plate to the substrate through precise control of the parallel distance between the printing plate and the substrate to achieve a dispersed arrangement of the droplets. Typical printing plates include curved plates (ex rollers) and flat plates with convex / concave / hollow ring dots and combinations of the above dots engraved on the surface.

[0074] The coating method of screen printing includes: engraving a dot array on the screen, passing the coating slurry through the screen by scraping, and arranging it in the form of a droplet array on the other side of the screen. Through the precise control of the parallel distance between the screen and the substrate, the micro droplets carried by the screen are transferred to the substrate to achieve a dispersed arrangement of the droplets.

[0075] The coating is carried out by contact dotting technology. The basic unit of this technology is a large number of branch channels connected to the flow channel. The branch channels have a structure that can carry micro droplets. The structure performs high-frequency reciprocating motion under mechanical drive, and the micro droplets contact and transfer to the substrate. Common mechanical drive methods include screw pump type or piston type.

[0076] Non-contact coating can realize non-contact coating technology. The basic principle is that the coating slurry in the flow channel passes through the micropores under the impetus of pump pressure / air pressure / mechanical force, and a high-frequency opening and closing unit may be included somewhere on the flow channel. Mechanical driving force includes derived thermal bubble, piezoelectric, sonic, and electromagnetic technologies. Some technologies do not include high-frequency opening and closing units, and instead use high-voltage static electricity, airflow, etc., which can cause the slurry liquid stream to split into micro droplets, such as electrohydrodynamic printing.

[0077] In a third aspect, the present invention provides a lithium ion battery comprising the lithium ion battery separator.

[0078] The lithium-ion battery has excellent electrochemical performance.

[0079] Optionally, the lithium-ion battery further includes a positive electrode sheet, a negative electrode sheet and an electrolyte, which is not limited in the present invention.

[0080] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0081] In the following examples and comparative examples, the softening point of the polymer was measured using a Vicat softening temperature tester, and the melting point of the polymer was measured using DSC.

[0082] Example 1 The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: (1) 15 parts by mass of polymethyl methacrylate with a solid content of 45% were mixed with 37 parts of deionized water, and stirred at 25°C and 500 r / min for 20 min; then 80 parts by mass of alumina and 100 parts of thickener (4wt.% CMC premixed aqueous solution) were added thereto, and stirred at 25°C and 1500 rpm for 1.5 h to obtain a ceramic slurry with a solid content of 40%. The ceramic slurry was coated on both sides of a polyethylene diaphragm (substrate) with a thickness of 5 μm, and after oven drying, a ceramic diaphragm with a heat-resistant coating of 2 μm thick on each surface was obtained, which was recorded as C1.

[0083] (2) 18 parts by mass of poly(meth)acrylate polymer particles (copolymer), 1 part of polyacrylate binder and 81 parts of deionized water were mixed and stirred at room temperature for 30 minutes to form a uniform slurry to obtain a first polymer slurry. The poly(meth)acrylate polymer particles (i.e., the first polymer) had a softening point of 55° C. and a median particle size of 4.5 μm.

[0084] 15 parts of polyurethane particles, 1 part of polyacrylate binder and 84 parts of deionized water were mixed by weight, and stirred at room temperature for 30 minutes to form a uniform slurry to obtain a second polymer slurry. The polyurethane particles (i.e., the second polymer) had a melting point or softening point of 107° C. and a median particle size of 3.8 μm.

[0085] (3) Screen printing: A screen with circular meshes of 80 mesh in diameter is prepared, with a mesh spacing of 1200 μm, and four adjacent meshes arranged in a square shape. Two screens are arranged in parallel, connected to a material box containing the first polymer slurry and a material box containing the second polymer slurry, respectively, and the meshes of the screens are arranged with a 600 μm offset. A scraper is used to transfer the first polymer slurry and the second polymer slurry through the meshes to one surface of the diaphragm C1 obtained in step (1), and the screen and the diaphragm C1 move in the same direction at the same speed. The coated diaphragm is dried in an oven at 70°C to obtain a lithium-ion battery diaphragm.

[0086] The lithium-ion battery separator prepared in this embodiment includes a PE substrate, a heat-resistant coating disposed on both surfaces of the substrate, and a polymer coating disposed on the surface of a heat-resistant coating. The polymer coating includes a plurality of dispersed dot structures, and the dot structures are arranged in a dot matrix, and the shape of the dot structures includes an island shape. The diameter of the circumscribed circle of the dot structure is Z, and within the range of 5Z as the radius with the center point of the circumscribed circle as the center of the circle, dot structures containing a first polymer and dot structures containing a second polymer are arranged at the same time. The number ratio of the dot structures containing the first polymer and the dot structures containing the second polymer is 1:1, and the shape of the outer contour of the positive projection of the dot structures containing the first polymer on the substrate is an ellipse, the diameter range of the circumscribed circle of the dot structures containing the first polymer (having multiple sizes) is 220μm~260μm, and the diameter range of the circumscribed circle of the dot structures containing the second polymer (having multiple sizes) is 230μm~280μm. As Figure 2 As shown, the diameters of the circumscribed circles of two adjacent dot-like structures are X and Y, respectively, and the distance between the centers of the circumscribed circles of the two is D, the larger number of X and Y is MAX, the smaller number of X and Y is MIN, D>1.25MAX and D<5×MAX, K=D / MAX=2.7. The distance between the centers of the circumscribed circles of two adjacent dot-like structures is 1200μm. The height of the dot-like structure is 2~8μm. The mass ratio of the first polymer to the second polymer in the polymer coating is 5.2:4.8. The total area coverage of the polymer coating on the substrate is 5%, and the single-sided loading of the polymer coating is 0.35g / m 2 .

[0087] like Figure 3 The figure shows the arrangement diagram of the dot-like structure in the lithium-ion battery separator prepared in this embodiment, in which the black solid dots represent the dot-like structure containing the first polymer, the white dots represent the dot-like structure containing the second polymer, and the connecting lines are used to illustrate the dot matrix arrangement of the dot-like structure. Among them, the shape of the figure formed by the connecting lines of the center points of the four adjacent dot-like structures containing the first polymer is a square, and the angle between the two adjacent sides in the figure is 90°. The shape of the figure formed by the connecting lines of the center points of the four adjacent dot-like structures containing the second polymer is a square, and the angle between the two adjacent sides in the figure is 90°. The dot-like structure containing the first polymer and the dot-like structure containing the second polymer are nested in the midpoint of the edge of the figure formed by the connecting lines.

[0088] Example 2 The method for preparing the lithium-ion battery separator provided in this embodiment is basically the same as that in Embodiment 1, except that the pore size and arrangement of the wire mesh holes are changed in step (3).

[0089] The lithium-ion battery separator prepared in this embodiment includes a PE substrate, a heat-resistant coating disposed on both surfaces of the substrate, and a polymer coating disposed on the surface of a heat-resistant coating. The polymer coating includes a plurality of dispersed dot structures, the dot structures are arranged in a dot matrix, and the shape of the dot structures includes an island shape. The diameter of the circumscribed circle of the dot structure is Z, and within the range of 5Z as the radius and the center point of the circumscribed circle as the center of the circle, dot structures containing the first polymer and dot structures containing the second polymer are arranged at the same time. The number ratio of the dot structure containing the first polymer and the dot structure containing the second polymer is 1:1, and the shape of the outer contour of the positive projection of the dot structure containing the first polymer on the substrate is an ellipse, and the diameter range of the circumscribed circle of the dot structure containing the first polymer (having multiple sizes) is 280μm~350μm, and the diameter range of the circumscribed circle of the dot structure containing the second polymer (having multiple sizes) is 300μm~350μm. The diameters of the circumscribed circles of two adjacent dot-like structures are X and Y, respectively. The distance between the centers of the circumscribed circles of the two adjacent dot-like structures is D. The larger of X and Y is MAX, and the smaller of X and Y is MIN. D>1.25MAX and D<5×MAX, K=D / MAX=4.3. The distance between the centers of the circumscribed circles of two adjacent dot-like structures is 1200μm. The height of the dot-like structure is 2~10μm. The mass ratio of the first polymer to the second polymer in the polymer coating is 5.5:4.5. The total area coverage of the polymer coating on the substrate is 10%, and the single-sided loading of the polymer coating is 0.5g / m 2 .

[0090] The dotted structure arrangement diagram of the lithium ion battery separator prepared in this embodiment is as follows: Figure 4 As shown. The black solid dots represent the dot-like structures containing the first polymer, the white dots represent the dot-like structures containing the second polymer, and the connecting lines are used to illustrate the dot matrix arrangement of the dot-like structures. The shape of the figure formed by the connecting lines of the center points of four adjacent dot-like structures containing the first polymer is a rectangle, and the angle between the two adjacent sides in the figure is 90°. The shape of the figure formed by the connecting lines of the center points of four adjacent dot-like structures containing the second polymer is a rectangle, and the angle between the two adjacent sides in the figure is 90°. The dot-like structures containing the first polymer and the dot-like structures containing the second polymer are nested in the midpoints of the sides of the figure formed by the connecting lines.

[0091] Example 3 The preparation method of the lithium-ion battery separator provided in this embodiment is basically the same as that in Embodiment 1, except that the aperture, arrangement and number of the mesh holes of the wire mesh are changed in step (3).

[0092] The lithium-ion battery separator prepared in this embodiment includes a PE substrate, a heat-resistant coating disposed on both surfaces of the substrate, and a polymer coating disposed on the surface of a heat-resistant coating. The polymer coating includes a plurality of dispersed dot structures, the dot structures are arranged in a dot matrix, and the shape of the dot structures includes an island shape. The diameter of the circumscribed circle of the dot structure is Z, and within the range of 5Z as the radius and the center point of the circumscribed circle as the center of the circle, dot structures containing the first polymer and dot structures containing the second polymer are arranged at the same time. The number ratio of the dot structure containing the first polymer and the dot structure containing the second polymer is 2:1, and the shape of the outer contour of the positive projection of the dot structure containing the first polymer on the substrate is an ellipse, and the diameter range of the circumscribed circle of the dot structure containing the first polymer (having multiple sizes) is 250μm~280μm, and the diameter range of the circumscribed circle of the dot structure containing the second polymer (having multiple sizes) is 250μm~280μm. The diameters of the circumscribed circles of two adjacent dot-like structures are X and Y, respectively. The distance between the centers of the circumscribed circles of the two adjacent dot-like structures is D. The larger of X and Y is MAX, and the smaller of X and Y is MIN. D>1.25MAX and D<5×MAX, K=D / MAX=4.3. The distance between the centers of the circumscribed circles of two adjacent dot-like structures is 1200μm. The height of the dot-like structure is 4~15μm. The mass ratio of the first polymer to the second polymer in the polymer coating is 6.3:3.7. The total area coverage of the polymer coating on the substrate is 16%, and the single-sided loading of the polymer coating is 0.6g / m 2 .

[0093] The dotted structure arrangement diagram of the lithium ion battery separator prepared in this embodiment is as follows: Figure 5 As shown. The black solid dots represent the dot-like structures containing the first polymer, the white dots represent the dot-like structures containing the second polymer, and the connecting lines are used to illustrate the dot matrix arrangement of the dot-like structures. The shape of the figure formed by the connecting lines of the center points of four adjacent dot-like structures containing the first polymer is a parallelogram, and the acute angle between the two adjacent sides in the figure is 55°. The shape of the figure formed by the connecting lines of the center points of four adjacent dot-like structures containing the second polymer is a parallelogram, and the acute angle between the two adjacent sides in the figure is 55°. The dot-like structures containing the first polymer and the dot-like structures containing the second polymer are nested in the center points of the quadrilateral formed by the connecting lines.

[0094] Example 4 The preparation method of the lithium-ion battery separator provided in this embodiment is basically the same as that in Embodiment 1, except that the aperture, arrangement and number of the mesh holes of the wire mesh are changed in step (3).

[0095] The lithium-ion battery separator prepared in this embodiment includes a PE substrate, a heat-resistant coating disposed on both surfaces of the substrate, and a polymer coating disposed on the surface of a heat-resistant coating. The polymer coating includes a plurality of dispersed dot structures, the dot structures are arranged in a dot matrix, and the shape of the dot structures includes an island shape. The diameter of the circumscribed circle of the dot structure is Z, and within the range of 5Z as the radius and the center point of the circumscribed circle as the center of the circle, dot structures containing the first polymer and dot structures containing the second polymer are arranged at the same time. The number ratio of the dot structure containing the first polymer and the dot structure containing the second polymer is 1:2, and the shape of the outer contour of the positive projection of the dot structure containing the first polymer on the substrate is an ellipse, and the diameter range of the circumscribed circle of the dot structure containing the first polymer (having multiple sizes) is 300μm~330μm, and the diameter range of the circumscribed circle of the dot structure containing the second polymer (having multiple sizes) is 300μm~330μm. The diameters of the circumscribed circles of two adjacent dot-like structures are X and Y, respectively. The distance between the centers of the circumscribed circles of the two adjacent dot-like structures is D. The larger of X and Y is MAX, and the smaller of X and Y is MIN. D>1.25MAX and D<5×MAX, K=D / MAX=3.5. The distance between the centers of the circumscribed circles of two adjacent dot-like structures is 1200μm. The height of the dot-like structure is 5~20μm. The mass ratio of the first polymer to the second polymer in the polymer coating is 3.3:6.7. The total area coverage of the polymer coating on the substrate is 33%, and the single-sided loading of the polymer coating is 0.9g / m 2 .

[0096] The dotted structure arrangement diagram of the lithium ion battery separator prepared in this embodiment is as follows: Figure 6 As shown. The black solid dots represent the dot-like structures containing the first polymer, the white dots represent the dot-like structures containing the second polymer, and the connecting lines are used to illustrate the dot matrix arrangement of the dot-like structures. The shape of the figure formed by the connecting lines of the center points of four adjacent dot-like structures containing the first polymer is a parallelogram, and the acute angle between the two adjacent sides in the figure is 55°. The shape of the figure formed by the connecting lines of the center points of four adjacent dot-like structures containing the second polymer is a parallelogram, and the acute angle between the two adjacent sides in the figure is 55°. The dot-like structures containing the first polymer and the dot-like structures containing the second polymer are nested in the center points of the quadrilateral formed by the connecting lines.

[0097] Example 5 The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: (1) 15 parts by mass of polymethyl methacrylate with a solid content of 45% were mixed with 37 parts of deionized water, and stirred at 25°C and 500 r / min for 20 min; then 80 parts by mass of alumina and 100 parts of thickener (4wt.% CMC premixed aqueous solution) were added thereto, and stirred at 25°C and 1500 rpm for 1.5 h to obtain a ceramic slurry with a solid content of 40%. The ceramic slurry was coated on one side of a polyethylene diaphragm (substrate) with a thickness of 9 μm, and after being dried in an oven, a ceramic diaphragm with a heat-resistant coating of 3 μm on the surface was obtained, which was recorded as C2.

[0098] (2) 4.3 parts by mass of poly(meth)acrylate polymer particles, 10 parts by mass of poly(vinylidene fluoride-hexafluoropropylene) polymer particles, 1 part by mass of polyacrylate binder, 0.5 parts by mass of thickener (sodium carboxymethyl cellulose) and 84.2 parts by mass of deionized water were mixed and stirred at room temperature for 30 minutes to form a uniform slurry to obtain a mixed polymer slurry. The softening point of the poly(meth)acrylate polymer particles (i.e., the first polymer) is 55°C and the median particle size is 4.5 μm. The melting point of the poly(vinylidene fluoride-hexafluoropropylene) polymer particles (i.e., the second polymer) is 155°C. The poly(vinylidene fluoride-hexafluoropropylene) polymer particles are secondary particles formed by agglomeration of primary particles, wherein the median particle size of the secondary particles is 8.6 μm and the median particle size of the primary particles is 220 nm.

[0099] (3) Gravure coating: Prepare a transfer roller containing a cylindrical convex dot array with a diameter of 300 μm, a convex dot spacing of 580-620 μm, and a hole array forming an angle of 60° with the long axis of the roller. Use a gravure roller to transfer the above-mentioned mixed polymer slurry from the material box to the transfer roller containing a circular convex dot array. The diaphragm C2 (porous substrate) obtained in step (1) is carried by a steel roller. The parallel spacing between the transfer roller and the steel roller is (porous substrate thickness + cylindrical convex dot height 67-97 μm). The transfer roller and the porous substrate move in the same direction at the same speed to transfer the above-mentioned mixed polymer slurry to the diaphragm C2 obtained in step (1). The coated diaphragm is dried in an oven at 60°C to obtain a lithium-ion battery diaphragm.

[0100] The lithium-ion battery separator prepared in this embodiment includes a PE substrate, a heat-resistant coating disposed on one surface of the substrate, and a polymer coating disposed on the surface of the heat-resistant coating. The polymer coating includes a plurality of dispersed dot structures, the dot structures are arranged in a dot matrix, and the shape of the dot structure includes a ring. The diameter of the circumscribed circle of the dot structure is Z, and the polymer coating contains a first polymer and a second polymer within the range of 5Z as the radius and the center point of the circumscribed circle as the center of the circle. The shape of the outer contour of the positive projection of the dot structure on the substrate is an ellipse, and the diameter range of the circumscribed circle of the dot structure (with multiple sizes) is 280μm~330μm. The diameters of the circumscribed circles of two adjacent dot structures are X and Y, respectively, and the distance between the centers of the circumscribed circles of the two is D, the larger number of X and Y is MAX, the smaller number of X and Y is MIN, D>1.25MAX and D<5×MAX, K=D / MAX=2.1. The distance between the centers of the circumscribed circles of two adjacent dot structures is 600μm. The height of the dot structure is 8~20μm. The mass ratio of the first polymer to the second polymer in the polymer coating is 3:7. The total area coverage of the polymer coating on the substrate is 22%, and the single-side loading of the polymer coating is 0.7 g / m 2 .

[0101] like Figure 7 The figure shown is the arrangement diagram of the dot structure in the lithium-ion battery separator prepared in this embodiment, wherein the figure formed by the connecting line of the center points of four adjacent dot structures is a rhombus with an acute angle of 60°, and the connecting line is for illustrating the dot matrix arrangement of the dot structure.

[0102] Example 6 The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: (1) Same as step (1) of Example 5.

[0103] (2) 1.2 parts by mass of polymethyl methacrylate polymer particles (homopolymer), 10 parts by mass of styrene butadiene rubber particles, 0.6 parts by mass of polyacrylonitrile binder, 0.4 parts by mass of thickener (sodium carboxymethyl cellulose) and 87.8 parts by mass of deionized water were mixed and stirred at room temperature for 30 minutes to form a uniform slurry to obtain a mixed polymer slurry. The softening point of the polymethyl methacrylate polymer particles (i.e., the first polymer) was 59°C and the median particle size was 3.7 μm. The softening point of the styrene butadiene rubber particles (i.e., the second polymer) was 105°C and the median particle size of the styrene butadiene rubber particles was 4.8 μm.

[0104] (3) Gravure coating: A micro-gravure roller containing honeycomb holes is prepared. The holes are regular hexagons with a side length of 400 μm, the hole center distance is 1200 μm, and four adjacent holes are arranged in a square. The mixed polymer slurry is transferred to the separator C2 obtained in step (1) using a micro-gravure roller. The micro-gravure roller and the separator C2 move in the same direction at the same speed. The coated separator is dried in an oven at 50°C to obtain a lithium-ion battery separator.

[0105] The lithium-ion battery separator prepared in this embodiment includes a PE substrate, a heat-resistant coating disposed on one surface of the substrate, and a polymer coating disposed on the surface of the heat-resistant coating. The polymer coating includes a plurality of dispersed dot structures, the dot structures are arranged in a dot matrix, and the shape of the dot structure includes a ring. The diameter of the circumscribed circle of the dot structure is Z, and within the range of 5Z as the radius and the center point of the circumscribed circle as the center of the circle, the polymer coating contains a first polymer and a second polymer. The shape of the outer contour of the positive projection of the dot structure on the substrate is an ellipse, and the diameter range of the circumscribed circle of the dot structure (with multiple sizes) is 400μm~420μm. The diameters of the circumscribed circles of two adjacent dot structures are X and Y, respectively, and the distance between the centers of the circumscribed circles of the two is D, the larger number of X and Y is MAX, the smaller number of X and Y is MIN, D>1.25MAX and D<5×MAX, K=D / MAX=3. The distance between the centers of the circumscribed circles of two adjacent dot structures is 1200μm. The height of the dot structure is 12~18μm. The mass ratio of the first polymer to the second polymer in the polymer coating is 8.3:1. The total area coverage of the polymer coating on the substrate is 37%, and the single-side loading of the polymer coating is 1.2 g / m 2 .

[0106] like Figure 8 The figure shown is the arrangement diagram of the dot structure in the lithium-ion battery separator prepared in this embodiment, wherein the figure formed by the connecting line of the center points of four adjacent dot structures is a square with an angle of 90°, and the connecting line is for illustrating the dot matrix arrangement of the dot structure.

[0107] Example 7 The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: (1) Same as step (1) of Example 5.

[0108] (2) 1.5 parts of polyvinyl acetate particles, 13.5 parts of polyvinylidene fluoride particles, 0.75 parts of polyacrylonitrile binder, 0.4 parts of sodium dodecyl sulfate and 83.85 parts of deionized water were mixed by weight, and stirred at room temperature for 30 minutes to form a uniform slurry to obtain a mixed polymer slurry. Among them, the softening point of polyvinyl acetate particles (i.e., the first polymer) is 38°C, and the median particle size of polyvinyl acetate particles is 5.8μm. The melting point of polyvinylidene fluoride particles (i.e., the second polymer) is 170°C, and the polyvinylidene fluoride particles are secondary particles formed by agglomeration of primary particles, wherein the median particle size of the secondary particles is 6.4μm, and the median particle size of the primary particles is 200nm.

[0109] (3) Inkjet printing: piezoelectric inkjet printing technology, RICOH-GH2220 inkjet printing valve, nozzle spacing in a single valve is 1000 μm, multiple valves are arranged in two rows horizontally, each row of nozzles forms a straight line arrangement with a spacing of 1000 μm, and the nozzle positions between the two rows are offset by 1000 μm. The mixed polymer slurry is passed through the nozzle, and the mixed polymer slurry is sprayed on the diaphragm C2 obtained in step (1). The coated diaphragm is dried in an oven at 80°C to obtain a lithium-ion battery diaphragm.

[0110] The lithium-ion battery separator prepared in this embodiment includes a PE substrate, a heat-resistant coating disposed on one surface of the substrate, and a polymer coating disposed on the surface of the heat-resistant coating. The polymer coating includes a plurality of dispersed point structures, the point structures are arranged in a dot matrix, and the shapes of the point structures include rings and islands. The diameter of the circumscribed circle of the point structure is Z, and the polymer coating contains a first polymer and a second polymer within the range of 5Z as the radius and the center point of the circumscribed circle as the center of the circle. The shape of the outer contour of the positive projection of the point structure on the substrate includes a circle and an ellipse, and the diameter range of the circumscribed circle of the point structure (with multiple sizes) is 380μm~400μm. The diameters of the circumscribed circles of two adjacent point structures are X and Y, respectively, and the distance between the centers of the circumscribed circles of the two is D, the larger of X and Y is MAX, the smaller of X and Y is MIN, D>1.25MAX and D<5×MAX, K=D / MAX=2.8. The distance between the centers of the circumscribed circles of two adjacent point structures is 1200μm. The height of the dot structure is 10~20μm. The figure formed by the center point connection of four adjacent dot structures is a square with an angle of 90°. The mass ratio of the first polymer to the second polymer in the polymer coating is 1:9. The total area coverage of the polymer coating on the substrate is 31%, and the single-sided loading of the polymer coating is 1.0g / m 2 .

[0111] Example 8 The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: (1) Same as step (1) of Example 5.

[0112] (2) 6 parts by mass of poly(meth)acrylate polymer particles, 6 parts by mass of polyacrylonitrile particles, 0.54 parts by mass of polyimide binder, 0.3 parts by mass of sodium dodecyl sulfonate and 87.16 parts by mass of deionized water were mixed and stirred at room temperature for 30 minutes to form a uniform slurry to obtain a mixed polymer slurry. The softening point of the poly(meth)acrylate polymer particles (i.e., the first polymer) was 55°C, and the median particle size was 2.8 μm. The softening point of the polyacrylonitrile particles (i.e., the second polymer) was 260°C, and the median particle size of the polyacrylonitrile particles was 3.2 nm.

[0113] (3) Mechanical impact pin printing: Using mechanical impact pin printing technology, high-frequency mechanical reciprocating motion drives the impact pin to impact the nozzle. The spacing between individual nozzles is 1200 μm. The nozzles are arranged horizontally in two rows. Each row of nozzles forms a linear arrangement with a spacing of 32400 μm. The nozzle positions between the two rows are offset horizontally by 1200 μm. The nozzle is connected to the above-mentioned mixed polymer slurry, and the slurry is sprayed on the diaphragm C2 obtained in step (1). The coated diaphragm is dried in a 70°C oven to obtain a lithium-ion battery diaphragm.

[0114] The lithium-ion battery separator prepared in this embodiment includes a PE substrate, a heat-resistant coating disposed on one surface of the substrate, and a polymer coating disposed on the surface of the heat-resistant coating. The polymer coating includes a plurality of dispersed dot structures, the dot structures are arranged in a dot matrix, and the shape of the dot structure includes a ring. The diameter of the circumscribed circle of the dot structure is Z, and the polymer coating contains a first polymer and a second polymer within the range of 5Z as the radius and the center point of the circumscribed circle as the center of the circle. The shape of the outer contour of the positive projection of the dot structure on the substrate is an ellipse, and the diameter range of the circumscribed circle of the dot structure (with multiple sizes) is 380μm~420μm. The diameters of the circumscribed circles of two adjacent dot structures are X and Y, respectively, and the distance between the centers of the circumscribed circles of the two is D, the larger of X and Y is MAX, the smaller of X and Y is MIN, D>1.25MAX and D<5×MAX, K=D / MAX=2.8. The distance between the centers of the circumscribed circles of two adjacent dot structures is 1200μm. The height of the dot structure is 10-20 μm. The figure formed by the line connecting the center points of four adjacent dot structures is a square with an angle of 90°. The mass ratio of the first polymer to the second polymer in the polymer coating is 5:5. The total area coverage of the polymer coating on the substrate is 28%, and the single-sided loading of the polymer coating is 0.8 g / m 2 .

[0115] Example 9 The method for preparing the lithium-ion battery separator provided in this embodiment is basically the same as that in Embodiment 8, except that step (1) is not performed, and in step (3) the slurry is sprayed on a PP separator without a heat-resistant coating.

[0116] Example 10 The preparation method of the lithium-ion battery separator provided in this embodiment is basically the same as that in Embodiment 8, except that the PP separator is replaced by a PE separator.

[0117] Comparative Example 1 The preparation method of the lithium ion battery separator provided in this comparative example comprises the following steps: (1) Same as step (1) of Example 1.

[0118] (2) Mix 15 parts of polyvinylidene fluoride-hexafluoropropylene polymer particles (melting point 155°C), 1 part of polyacrylate binder, 0.5 parts of thickener and 83.5 parts of deionized water, and stir at room temperature for 30 minutes to form a uniform slurry to obtain a polymer slurry. The average particle size of the secondary particles of the polyvinylidene fluoride-hexafluoropropylene polymer is 8.6μm, and the average particle size of the primary particles is 220nm. Use a rotary spraying device to evenly spray the polymer slurry on the diaphragm C1 obtained in step (1). The coated diaphragm is dried in an oven at a drying temperature of 60°C. After coating and drying, a lattice structure polymer coating is obtained, and the single-sided loading of the polymer is 0.5g / m 2 , with a coverage rate of 12%.

[0119] Comparative Example 2 The preparation method of the lithium ion battery separator provided in this comparative example comprises the following steps: (1) Same as step (1) of Example 1.

[0120] (2) Mix 12 parts of poly(meth)acrylate polymer particles (softening point is 55°C), 0.54 parts of polyimide binder, 0.3 parts of sodium dodecyl sulfate and 87.16 parts of deionized water, and stir at room temperature for 30 minutes to form a uniform slurry to obtain a polymer slurry. The average particle size of the poly(meth)acrylate polymer particles is 2.8 μm. Use a roller coating device to evenly coat the above polymer slurry on the diaphragm C1 obtained in step (1). The coated diaphragm is dried in an oven at a drying temperature of 60°C. After coating and drying, a lattice structure polymer coating is obtained, and the single-sided loading of the polymer is 0.5 g / m 2 , with a coverage rate of 12%.

[0121] Comparative Example 3 The preparation method of the lithium ion battery separator provided in this comparative example is basically the same as that of Example 8, except that no poly(meth)acrylate polymer particles are added in step (2), and the mass fraction of polyacrylonitrile particles is replaced by 12 parts.

[0122] Comparative Example 4 The preparation method of the lithium ion battery separator provided in this comparative example is basically the same as that of Example 8, except that no polyacrylonitrile particles are added in step (2), and the mass fraction of the poly(meth)acrylate polymer particles is replaced by 12 parts.

[0123] Adhesion test: The lithium-ion battery separators and lithium iron phosphate pole pieces prepared in each embodiment and each comparative example were stacked and hot pressed respectively. The hot pressing conditions were: 1 MPa, 95° C., 5 min. The test results are shown in Table 1.

[0124] Table 1 Adhesion test results

[0125] Air permeability test: The lithium-ion battery separators and silicone release films prepared in each embodiment and each comparative example were stacked and hot-pressed for compounding, and the hot-pressing conditions were: 1MPa, 95°C, 5min. The air permeability values ​​before and after compounding were tested, and the results are shown in Table 2. Among them, the air permeability value before compounding refers to the air permeability value of each separator prepared in each embodiment and each comparative example before hot-pressing compounding; the air permeability value after hot-pressing compounding refers to the air permeability value of each separator after the silicone release film is peeled off after hot-pressing compounding. The air permeability value is characterized by the Gurley value, which refers to the time required for a specific amount of air to pass through a membrane of a specific area at a specific pressure (standard Gruley: the time it takes for 100mL of gas to pass through a 1 square inch membrane at a pressure of 4.88 inches of water column).

[0126] Table 2 Air permeability test results

[0127] It can be seen from Table 1 and Table 2 that the diaphragm prepared in each embodiment has good adhesion to the electrode, and after hot pressing, the air permeability value increases at a low level (which means that the diaphragm in each embodiment does not produce serious pore blockage after hot pressing). This shows that the first polymer and the second polymer work together to give play to the advantages of different polymer materials, and can reduce the pore blockage problem of the diaphragm and the heat-resistant coating while improving the adhesion between the diaphragm and the electrode.

[0128] However, only a single polymer is used in each comparative example, and its performance cannot be achieved in terms of adhesion and clogging.

[0129] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A lithium ion battery separator, characterized in that: It comprises a substrate and a polymer coating disposed on at least one surface of the substrate, wherein the polymer coating comprises a plurality of dispersed dot structures, and the dot structures have a ring shape and / or an island shape; The diameter of the circumscribed circle of the dot-like structure is Z, and within the range of 8Z with the center point of the circumscribed circle as the center of the circle and the radius as the center point, the polymer coating contains a first polymer and a second polymer; The melting point or softening point of the first polymer is ≤90°C; The melting point or softening point of the second polymer is >90°C.

2. The lithium-ion battery separator according to claim 1, characterized in that: The diameter of the circumscribed circle of the dot-like structure is 100 μm to 1000 μm.

3. The lithium-ion battery separator according to claim 1, characterized in that: The diameters of the circumscribed circles of two adjacent dot-like structures are X and Y respectively, and the distance between the centers of the two circumscribed circles is D, wherein D is greater than the maximum value of X and Y, and D is less than 5 times the maximum value of X and Y; Alternatively, D is greater than 1.25 times the maximum value of X and Y.

4. The lithium-ion battery separator according to claim 1, characterized in that: The distance between the centers of the circumscribed circles of two adjacent dot-shaped structures is 100 μm to 1500 μm.

5. The lithium-ion battery separator according to claim 1, characterized in that: At least one of the following conditions is met: (1) The shape of the outer contour of the orthographic projection of the dot-like structure on the substrate includes at least one of a circle, an ellipse and a quasi-circle; (2) The dot-like structures are arranged in a dot matrix; (3) The height of the dot-like structure is 1 μm to 20 μm.

6. The lithium-ion battery separator according to claim 1, characterized in that: At least one of the following conditions is met: (1) the first polymer includes at least one of polyvinylidene chloride, polyacrylate, polyvinyl acetate, polyoxyethylene, polyvinylidene fluoride, polyoxypropylene, styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, acryl rubber, butyl rubber, fluororubber, polyepichlorohydrin, polyphosphazene, polyvinylpyridine and styrene-butadiene rubber; (2) The melting point or softening point of the first polymer is 30°C to 90°C; (3) The median particle size of the first polymer is 0.1 μm to 20 μm; (4) the second polymer comprises at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene polymer, polyacrylate, polystyrene, polyacrylonitrile, polytetrafluoroethylene, polymethacrylate, ethylene-vinyl acetate copolymer, polyester, polyamide, polyurethane, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene-acrylate copolymer, acrylated styrene-butadiene copolymer, phenolic resin, epoxy resin, polyvinyl pyrrolidone and polysulfone; (5) The median particle size of the second polymer is 0.1 μm to 20 μm; (6) The mass ratio of the first polymer to the second polymer in the polymer coating is 0.001-99.999:0.001-99.

999.

7. The lithium-ion battery separator according to claim 1, characterized in that: At least one of the following conditions is met: (1) The polymer coating has an area coverage of 5% to 40% on the substrate; (2) The single-sided loading of the polymer coating is 0.2 g / m 2 ~1.5g / m 2 .

8. The lithium-ion battery separator according to claim 1, characterized in that: At least one of the following conditions is met: (1) The substrate includes at least one of PE, PP, non-woven fabric, PET, PVDF, PU, ​​PA, PI, organic-inorganic blended film and PP / PE / PP composite film; (2) The polymer coating further comprises at least one of a binder, a dispersant and a thickener; (3) A heat-resistant coating is also included between the substrate and the polymer coating, and the heat-resistant coating contains an inorganic material, and the inorganic material includes at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

9. The method for preparing a lithium ion battery separator according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: coating a first slurry containing a first polymer and a second slurry containing a second polymer on at least one surface of a substrate respectively, and then drying.

10. A lithium ion battery, characterized in that: Comprising the lithium ion battery separator as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Polymer slurry, composite diaphragm and preparation method thereof

    CN109994695A

  • Separator for secondary battery, manufacturing method therefor, and lithium secondary battery comprising same

    CN113841290A

  • Lithium ion battery composite coating diaphragm and preparation method thereof

    CN115832624A

  • Battery, and electrochemical device and electronic device comprising same

    CN116979219A

  • Diaphragm and lithium ion secondary battery containing diaphragm

    CN210156470U

Cited By

  • Battery diaphragm, preparation method thereof and battery comprising battery diaphragm

    CN121484382A